Comparing synonymous adjectives in Vietnamese and English - Vo, Phuong (Práticas Educativas, Memórias e Oralidades - Rev. Pemo, 2024)
Vietnamese and English have many similarities and differences in using synonyms to express comparisons. The goal of the research is to analyze semantic similarities between Vietnamese and English. Researching this topic is done to clarify the expressions of the two languages to make the study of specialized terminology more convenient. The article will focus on clarifying theoretical basis issues, research methods, and research questions. It will also aim to elucidate the similarities in describing human qualities and the similarities and differences between synonyms of absolute characteristics between Vietnamese and English, drawing upon the corpus of idioms and proverbs in Oxford Advanced Learner's Dictionary of Diana Lea.